Left-invertible Linear Transformations - Gezahagne Mulat Addis (International Journal of Mathematics And its Applications, 2015)
In this paper we consider a linear transformation $T$ of an $n$ -dimensional vector space V into an $m$-dimensional vectorspace W and we provide necessary and sufficient conditions for ${T}$ to have an inverse from the left side. Moreover, we characterize the class of all left inverses of ${T}$.